Reinforce the surface properties of domestic garbage activated carbon by low temperature plasma accustomed in energy storage applications - Vijayalakshmi K.A; sowmiya K C (Zaštita Materijala)
Since activated carbon is a highly porous material with a sizable internal surface area, it is simple to adsorb a wide range of substances when used in energy storage devices, sewage treatment, water purification, catalyst, food processing and other applications. This work focuses on the viability of using mixed fruit peels as a precursor for the carbonization process with physical activation to produce activated carbon. The Phase confirmation was examined using X-ray diffraction (XRD). Fourier transform infrared spectrometer (FTIR) concludes the functional groups present in mixed fruit peels activated carbon. Field emission scanning electron microscopy (FESEM) was used to analyze the morphological makeup and textural traits of the activated carbon that was produced. Energy Dispersive X-Ray Analysis (EDX) shows the elemental composition of nano powdered carbon. Raman spectroscopy confirms the presence of graphene that appears at 1580cm-1. Electrochemical Impedance Spectroscopy (EIS) and Nyquist plot in order to evaluate the conductivity performance over the frequency range of 1mHz to 10 kHz, measurements were used.